A new microbombyliid Mythenteles rameli sp.n. (Diptera, Mythicomyiidae) from Northern Greece - Gibbs, David (Zootaxa, 2009)
A new species of the microbombyliid genus Mythenteles, M. rameli Gibbs, sp. n. is described from northern Greece with full illustrations of the male and female genitalia.